Risk factors associated with cisplatin‐induced ototoxicity in Japanese patients with solid tumors - Hideaki Okada; Koichi Kitagawa (Cancer Medicine, 2023)
Abstract Background Cisplatin, a first‐generation platinum agent, is used for managing various cancers and is associated with dose‐dependent side effects of hearing impairment and tinnitus. However, the safety of high‐dose cisplatin in hearing impairment, has not been fully investigated in Japan. Methods We performed pure‐tone threshold audiometry before and every 3–4 weeks after chemotherapy for patients receiving cisplatin‐containing chemotherapy between April 2015 and October 2017 at Kobe Minimally Invasive Cancer Center. Hearing impairment was evaluated prospectively using the National Cancer Institute Common Terminology Criteria for Adverse Events version 4.0. Results We enrolled 100 patients and analyzed 96 patients for whom post‐chemotherapy audiometry could be performed. The median patient age was 65 years, and most patients were male (75). The cancer types were as follows: esophageal, 36; head and neck, 35; lung, 23; and gastric, 2. Cisplatin monotherapy and combination therapy were administered to 33 and 63 patients, respectively. A single cisplatin dose was 60–100 mg/m2; the median number of doses and total dose were 3 and 240 mg/m2, respectively. Additionally, 78 and 18 patients were treated with concurrent chemoradiotherapy and chemotherapy alone, respectively. Twenty‐seven patients had grade 2 or higher hearing impairment. Furthermore, the prevalence was significantly higher in patients receiving a total dose of ≥300 mg/m2. Twenty and 32 patients were aware of deafness and tinnitus, respectively. Conclusion No patient discontinued treatment owing to hearing impairment. The total cisplatin dose was considered related to post‐treatment hearing impairment frequency in Japanese patients. However, routine audiometric monitoring is recommended during high‐dose cisplatin‐based chemotherapy.